Generation Z Perceived Elements of Wine Tourism Memorable Experience: A Qualitative Approach - Aikaterini VASSILIKOPOULOU; Irene (Eirini) KAMENIDOU; Spyridon MAMALIS (Communications of International Proceedings, 2021)
Wine tourism has been rapidly grown during the last decades in many countries (e.g., Italy, France, China). According to past studies, wine tourists expect more than testing and buying wine. As many researchers emphasize, wine tourists seek a "unique and memorable experience," and focus on "added value". The relevant literature reveals that only few studies have examined wine tourism from the wine tourist perspective and have taken into consideration the concept of experience, especially focusing on young people, particularly the Generation Z (Gen Zers) consumers. Based on the above, this study aims at exploring Gen Zers perceptions on wine tourism in Greece and detect the main characteristics that would create a unique and memorable experience. A qualitative research approach was implemented via 18 in-depth asynchronous online interviews. Results demonstrate the significant role of the tour guide as well and the importance of the ambient environment. Wine tourists also aim at escaping from everyday routine and relax through their visit in a winery. Finally, any “extras” (e.g., food) offered by the winey are highly appreciated. Wineries could incorporate perceived aspects of a unique experience in their marketing strategy to attract new tourists and build loyalty.
Keywords: Wine Tourism; Wineries; Consumers; Experience; Perceptions